APARELHOS PRIVADOS DE HEGEMONIA E O PROCESSO DE IMPLEMENTAÇÃO DA BASE NACIONAL COMUM CURRICULAR (BNCC) NO ESTADO DO PARANÁ - RUPPEL, JUSSARA DE FÁTIMA IVANSKI (2023)
This research has as aim at analyzing hegemony private apparatuses acting ways and implementation process of the Common National Curriculum Base - BNCC in its Portuguese acronym – in the State of Paraná. As Hegemony private apparatuses – APHE in Portuguese acronym, are considered associations, institutes, political parties, around which collective aspirations are organized, either from dominant or dominated groups. These APHEs are situated in the State model, considered by Gramsci as integral, constituted by political and civil societies. Searching for understanding this movement, the dissertations is organized from its main goal: investigating different acting ways of private apparatuses in BNCC implementation process in municipal education networks (Early years) of the State of Paraná. The following problem was designed: How is the performance of private apparatuses characterized in BNCC implementing process in the State of Paraná? As a result of the problem, other questions permeate the investigation: Which private apparatuses are present in this BNCC implementation process and what are their relationships in the governmental and private spheres? What are the strategies for action within the scope of municipal networks? To base the study, historical-dialectical materialism was used as a method, in the sense of promoting the understanding of the object from the totality and its contradictions. The text is based on Gramsci, specifically on his categories of State and private devices of hegemony, understanding that they are factors which direct educational policies. It also relies on authors who deal with curriculum and educational policy, as well as research related to the BNCC, starting from mapping academic production, with articles, theses, and dissertations. Therefore, it should be noted that this research has a bibliographic and documental character, based on public sources. Within the methodological aspects used in the corpus of this study, the materials available on the website of the National Union of Municipal Directors - UNDIME Paraná, Secretariat of State and Education do Paraná - EED, and the website of Movimento pela Base - MPB, which have been regulating the BNCC implementation at national level. This research is presented in three chapters: the first one sought to analyze the definition of the State supported by Gramsci, understanding that it is formed by political and civil societies, and that in this model, the hegemony private apparatuses act and present themselves as private agents, drivers, and organizers of policies in the educational environment. In this chapter, emphasis is placed on the survey of academic production as a way of building contributions on what has already been written on the theme. The second chapter highlights the organization around the preparation of the BNCC document, private apparatuses which stood out in this context, and the influence of these agents in its implementation. Finally, chapter three identifies the main action strategies of hegemony private apparatuses in the BNCC implementation in the State of Paraná. Technological use of digital platforms is emphasized as a resource to give direction to the implementation of the BNCC curricular policy in progress in the Brazilian states. As the implementation of the BNCC is not a disjointed process, it is not specially about specific municipalities, but it seeks to cover data referring to the articulation of several hegemony private apparatuses and segments of the public sphere around this implementation, at Basic Education level, Elementary School – Early years. It is intended that the study may trigger new research and concerns, since the results allowed to conclude that hegemony private apparatuses have been directing the BNCC implementation process in the municipalities of the State of Paraná. Their strategies surround themselves with solutions in BNCC implementation through digital platforms addressed to teacher training, planning and didactic material, identified as a path to educational quality.